2004
DOI: 10.1051/apido:2004050
|View full text |Cite
|
Sign up to set email alerts
|

Harmonized methods of melissopalynology

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
335
0
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(401 citation statements)
references
References 11 publications
(14 reference statements)
1
335
0
13
Order By: Relevance
“…The pollinic profiles determined showed that in 61 honey samples it was possible to identify between 4 and 9 different pollens, in 3 honey samples 3 different pollens were detected and, finally, in only 1 sample 2 different pollens were found. Independently of their colours and based on their pollinic profiles and on the relative abundance of each pollen [34,35], the 65 honey samples were classified as Castanea, Echium, Erica, Lavandula, Prunus and Rubus monofloral honey and, further split according to the 3 main colour groups previously defined: white, amber and dark. Table 2 presents information concerning harvest year, colour classification and pollinic profile (considering only the 3 pollens most predominante) of the honey samples analysed, which enables a detailed overview of the wide variability found for these two important honey characteristics.…”
Section: Honey Colour and Floral Origin Classificationsmentioning
confidence: 99%
“…The pollinic profiles determined showed that in 61 honey samples it was possible to identify between 4 and 9 different pollens, in 3 honey samples 3 different pollens were detected and, finally, in only 1 sample 2 different pollens were found. Independently of their colours and based on their pollinic profiles and on the relative abundance of each pollen [34,35], the 65 honey samples were classified as Castanea, Echium, Erica, Lavandula, Prunus and Rubus monofloral honey and, further split according to the 3 main colour groups previously defined: white, amber and dark. Table 2 presents information concerning harvest year, colour classification and pollinic profile (considering only the 3 pollens most predominante) of the honey samples analysed, which enables a detailed overview of the wide variability found for these two important honey characteristics.…”
Section: Honey Colour and Floral Origin Classificationsmentioning
confidence: 99%
“…Further work involving a more complete characterization of honey samples by classical analysis (physicochemical, melissopalynological and organoleptic techniques) for confirmation of honey identification [13][14][15], may clarify the results obtained as response of the present electronic device. On the other hand, the influence of the degree of predominance of a pollen type (for instance, samples with pollen predominance higher than 80%) on the differentiation provided by the device deserves further investigation, although it is probably difficult to obtain samples with this characteristic in large numbers.…”
Section: Resultsmentioning
confidence: 93%
“…In general, a honey sample can be classified as Lavandula monofloral honey if its Lavandula pollen content is higher than 15%, and as Erica or Echium monofloral honey if its respective pollen content is higher than 45% [12,13]. Large variations in pollen content are the result of large differences in the botanical composition of ecosystems around the apiaries.…”
mentioning
confidence: 99%
“…9 Pollen and honey type identification were carried out according to the Harmonized methods of melissopalynology. 10 The identification and counting of pollen grains was performed under Hund h 500 (Wetzlar, Germany) light microscope attached to a digital camera (Motic m 1000) and coupled to an image analysis system (Motic Images Plus software) for morphometric analysis of pollen grains (at 400 × magnification). Pollen grains were identified using personal reference pollen collection in the form of native preparations and literature data.…”
Section: Generalmentioning
confidence: 99%